Salivary IgA as a Surrogate Biomarker for Microbial Infections in Postoperative Patients Receiving Chemo-Radio-Therapy for Head and Neck Cancer - Chavan, Preeti; Bhat, Vivek; Joshi, Amit; Gupta, Tejpal; Murthy, Vedang; Noronha, Vanita; Rathish, Divya; Prabhash, Kumar (Journal of Laboratory Physicians, 2023)
Objective Radiotherapy (RT) and chemotherapy (CT) are important treatment options in patients with head and neck cancers. A common complication of this is microbial colonization or infection of mucosal surfaces. These infections may commonly be due to bacteria or yeasts. Salivary proteins with their buffering activity and immunoglobulin, especially immunoglobulin A (IgA), protect oral tissue, mucosal surfaces, and teeth from various microorganisms. This study characterizes the common microorganisms encountered and evaluates the role of salivary IgA in predicting microbial infections in this group of patients with mucositis.Methods A total of 150 adult head and neck cancer patients on CTRT were evaluated at baseline and at the end of 3 and 6 weeks, respectively. Oral swabs collected from buccal mucosa were processed in the microbiology laboratory for the presence of microorganisms. Saliva was processed for IgA level estimation on Siemens Dimension Automated biochemistry analyzer.Results Pseudomonas aeruginosa and Klebsiella pneumoniae were the most common organisms found in our patients, followed by Escherichia coli and group A beta-hemolytic Streptococci. A significant increase (p = 0.0203) in the incidence of bacterial infection was observed in post-CTRT patients (61%) compared to pre-CTRT patients (49.33%). There was significant increase in levels of salivary IgA (p = 0.003) in patients with bacterial and fungal infection (n = 135/267) when compared to those in samples showing no growth (n = 66/183).Conclusion A significant increase in the incidence of bacterial infection in post-CTRT patients was observed in this study. This study also indicated that postoperative head and neck cancer patients with oral mucositis that developed an infection were associated with high salivary IgA levels, and it may serve as a surrogate biomarker of infection in these patients.
Keywords: mucositis; IgA levels; fungal infection; bacterial infection; biomarker